OsHK3 is a crucial regulator of abscisic acid signaling involved in antioxidant defense in rice. Issue 2 (29th July 2014) - Wen, Feng; Qin, Tingting; Wang, Yao; Dong, Wen; Zhang, Aying; Tan, Mingpu; Jiang, Mingyi
Abstract In this study, the role of the rice (Oryza sativa L.) histidine kinase OsHK3 in abscisic acid (ABA)‐induced antioxidant defense was investigated. Treatments with ABA, H2O2, and polyethylene glycol (PEG) induced the expression of OsHK3 in rice leaves, and H2O2 is required for ABA‐induced increase in the expression of OsHK3 under water stress. Subcellular localization analysis showed that OsHK3 is located in the cytoplasm and the plasma membrane. The transient expression analysis and the transient RNA interference test in rice protoplasts showed that OsHK3 is required for ABA‐induced upregulation in the expression of antioxidant enzymes genes and the activities of antioxidant enzymes. Further analysis showed that OsHK3 functions upstream of the calcium/calmodulin‐dependent protein kinase OsDMI3 and the mitogen‐activated protein kinase OsMPK1 to regulate the activities of antioxidant enzymes in ABA signaling. Moreover, OsHK3 was also shown to regulate the expression of nicotinamide adenine dinucleotide phosphate oxidase genes, OsrbohB and OsrbohE, and the production of H2O2 in ABA signaling. Our data indicate that OsHK3 play an important role in the regulation of ABA‐induced antioxidant defense and in the feedback regulation of H2O2 production in ABA signaling.